Implementasi Kebijakan Perpres No. 68 Tahun 2022 di Dinas Pendidikan Sumatera Utara - Ichsanul Arifin Siregar; Budi Hartono; Isnaini Isnaini (Mahesa Research Center, 2023)
The purpose of this research is to analyze the Implementation of Presidential Decree No. 68 of 2022 concerning Revitalization of Vocational Education and Vocational Training at the Education Office of North Sumatra Province and the factors that become obstacles. The research method used is descriptive method, while the data analysis technique uses descriptive qualitative. The results of this study indicate that in terms of communication, the implementation of Presidential Decree Number 68 of 2022 concerning Revitalization of Vocational Education and Vocational Training (Studies at the Education Office of North Sumatra Province) has proceeded according to existing theory although there are still obstacles. In terms of resources, the implementation of Presidential Decree Number 68 of 2022 concerning Revitalization of Vocational Education and Vocational Training (Studies at the Education Office of North Sumatra Province) has proceeded according to existing theory, although there are still obstacles. From a disposition perspective, the implementation of Presidential Decree number 68 of 2022 concerning the revitalization of vocational education and vocational training (Studies at the Education Office of North Sumatra Province) has proceeded according to theory although there are still obstacles. In terms of bureaucratic structure, the implementation of Presidential Regulation Number 68 of 2022 concerning Revitalization of Vocational Education and Vocational Training (Studies at the Education Office of North Sumatra Province) has proceeded according to existing theory, although there are still obstacles.